Externalities in an endogenous growth model with social and natural capital - Roseta-Palma, C.; Ferreira-Lopes, A.; Sequeira, T. N. (Ecological Economics, 2010)
Models of economic growth are typically based on the use of one or more stocks of productive assets to create goods for utility-generating consumption. The roles played by man-made capital, natural capital, and human capital have been explored in the literature, and more recently the notion of social capital has been brought to the fore. This paper provides an attempt to construct an inclusive model of growth, analyzing externalities and distortions due to market failures linked with social capital and environmental problems.